Brainstorming to Improve Students' English Skills in the English Education Study Program at Islamic University of Ahmad Dahlan - Syukri, Muhammad; Bahrun, St. Rahmaniah; Amin, Fatimah Hidayahni (Universitas Islam Ahmad Dahlan (UIAD), 2023)
Today, in higher education, as at the university level, the learning process is still evolving. The objective of this study is to determine how to use the brainstorming concept to help students, particularly those who are already in semester 5, improve their English language skills. In this way, knowledge that may explicitly examine the degree of function is studied and explored by students in order to help them understand the concept of learning. Research design is use quantitative and survey as an approach whereas observation and questionnaire to collecting data. The result shows that brainstorming method was effective in impoving the students’ language skills especially for the 5 grade English learning program.Brainstorming talks about two possibilities of memory, short-term memory (STM) and long-term memory (LTM), as it is said to stimulate the minds of learners to activate creative thinking skills to build new ideas by connecting new knowledge with old, to build new links, to rearrange or reverse knowledge, to make connections between different concepts, to form make new connections or apply knowledge to a new field for learners to strike a balance.This research recommended the subsequent investigation to develop the method especially brainstorming for improving the students’ English skills.